Umsetzung von verbindlichen Flächensparzielen im Rahmen der räumlichen Planung - Lutke Blecken; Robert Böhnke; Gabriel Götze; Jens-Martin Gutsche; Wolfgang Köck; Thomas Preuß (Raumforschung und Raumordnung)
New land use for settlement and transport exceeds the federal government’s “below 30 ha/day” target. Varial federal states have incorporated this target into their own state targets. However, there has not been any operationalization in the form of binding targets at state, regional or municipal level to date. Operationalizing a binding quota system could involve trading land certificates (using an environmental economic approach) and spatial planning (using a regulatory approach). The analysis of land certificates trading was conducted through the “land trading simulation game” pilot project. However, there is no implementation or organizational model for operationalization using a spatial planning approach. To fill this gap, this paper presents a concept for implementing binding land-saving targets within the framework of spatial planning. It contains statements on the determination of a binding total volume of land quotas, the distribution between the federal and state governments, the distribution at state level to municipalities, the application of the quotas in planning procedures, the administration by “quota authorities” and the necessary accompanying measures.